Switched Capacitor Equivalent of Frequency Dependent Negative Resistor - Mikula, J.; Dostal, T. (Radioengineering Society, 1993)
A new circuit of frequency dependent negative resistor (FDNR), derived using an almost linear s-z transformation in a four phase switched capacitor (SC) network is presented.
Keywords: circuit theory; switched capacitor networks; frequency dependent negative resistors